2020
DOI: 10.4049/jimmunol.1900658
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Choline Kinase α–Mediated Choline Metabolism Supports the Prolonged Survival of TRAF3-Deficient B Lymphocytes

Abstract: Specific deletion of the tumor suppressor TRAF3 from B lymphocytes in mice leads to the prolonged survival of mature B cells and expanded B cell compartments in secondary lymphoid organs. In the current study, we investigated the metabolic basis of TRAF3-mediated regulation of B cell survival by employing metabolomic, lipidomic, and transcriptomic analyses. We compared the polar metabolites, lipids, and metabolic enzymes of resting splenic B cells purified from young adult B cell–specific Traf3−/− and litterma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 80 publications
2
22
0
Order By: Relevance
“…However, given the lack of CHKA gene amplification, it remained unknown what oncogenic alterations and signaling pathways cause the elevated expression of CHKA in B cell malignancies. Addressing this gap in knowledge, we recently made an interesting finding that deletion of the tumor suppressor gene TRAF3 leads to up-regulation of Chka at mRNA and protein levels in both mouse and human models of B cell malignancies [ 59 ].…”
Section: Elevated Chkα Expression and Choline Metabolism In B Cell Malignanciesmentioning
confidence: 99%
See 4 more Smart Citations
“…However, given the lack of CHKA gene amplification, it remained unknown what oncogenic alterations and signaling pathways cause the elevated expression of CHKA in B cell malignancies. Addressing this gap in knowledge, we recently made an interesting finding that deletion of the tumor suppressor gene TRAF3 leads to up-regulation of Chka at mRNA and protein levels in both mouse and human models of B cell malignancies [ 59 ].…”
Section: Elevated Chkα Expression and Choline Metabolism In B Cell Malignanciesmentioning
confidence: 99%
“…In an effort to elucidate the metabolic basis of TRAF3-mediated regulation of mature B cell survival, we performed metabolomic, lipidomic and transcriptomic profiling to compare the metabolism of resting splenic B cells purified from young adult B- Traf3 −/− and littermate control mice. We found that multiple metabolites, lipids and enzymes regulated by TRAF3 in B cells are clustered in the choline metabolic pathway [ 59 ]. Using stable isotope labeling, we showed that the biosynthesis of P-Cho and PC species (32:2 and 34:3) is increased in Traf3 −/− B cells, which is mediated by the up-regulated expression of Chkα [ 59 ].…”
Section: Elevated Chkα Expression and Choline Metabolism In B Cell Malignanciesmentioning
confidence: 99%
See 3 more Smart Citations